Cover Image. Issue 5 (25th September 2021) - Kolvenbag, Geert; Scott, Mark
Abstract : Cover caption : The cover image is based on the Original Article The Myth of Mitochondrial DNA and Race Performance in Racing Pigeons by Geert Kolvenbag and Mark Scott. https://doi.org/10.1002/vms3.494 .